CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN SAINS-FISIKA SMP - Wasis Wasis (Jurnal Cakrawala Pendidikan, 2006)
AbstractAny educational process implied by contextual teaching and learning(CTL) aims at helping students comprehension of the academic materials they are studying by connecting academic subjects with the contexts of their daily life. The present article is based on a research which developed a set of instructional materials to help teachers and their students achieve that aim.The instructional materials developed were adapted from a model submitted by Thiaragajan et al., which includes the steps of defining, designing, and developing. Assessment of the materials was done through experts judgment on and teachers and students responses to the materials. The final revised set of the materials were tried out at a state junior high school, SMPN 23, in Surabaya. During the try-out, teachers and students activities were observed and quantitatively and qualitatively analyzed.The results of the research show that the instructional materials (1) have the characteristics of (a) connecting the subject matter with daily life, (b) having been developed with attention paid to students learning styles, (c) developing higher-order thinking, (d) reflecting interest in students prior knowledge, (e) supporting the shaping of democratic and interactive learning situations, (f) providing teachers with more ease in their work, and (g) making more students like studying physics and (2) can help students achieve mastery learning.Key words: CTL, instructional materials for CTL